(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
Anemia among adolescent girls remains a major nutritional issue in disaster-prone areas, largely due to limited food access and poor dietary habits. This community service program aimed to improve nutritional knowledge and awareness among adolescent girls at SMKN 1 Sigi, Central Sulawesi, as part of efforts to prevent anemia and strengthen food security. The intervention utilized a participatory education approach through video-based learning materials that delivered messages on balanced nutrition, iron-rich foods, and the importance of iron supplementation. Thirty-two participants were involved in the activity, and their knowledge was measured using pre-test and post-test questionnaires. Data were analyzed using the Paired Sample t-test with a significance level of p < 0.05. The results showed a significant improvement in the mean knowledge score, increasing from 39.06 ± 15.94 before the intervention to 76.88 ± 11.48 after the intervention (p = 0.000). These findings indicate that video-based nutrition education is an effective and practical strategy to enhance knowledge and awareness about anemia prevention and food security among adolescent girls living in disaster-prone areas.